O jogo de RPG como ferramenta auxiliar de aprendizagem na disciplina de Ciências - Santos, Luiz Otávio Silva (2003)
ON reflecting the traditional teaching approach, characterized by non-dynamic and descriptive methods that still persists in schools at the present time, associated to social living enrichment has motivated the search for new techniques to stimulate students in the process of teaching, such as roleplaying games, known as RPG, already being used in various school disciplines. Considering the amount of themes in general sciences and in biology, in particular that could be explored through RPG our purpose was to develop a game to be used as a learning complementary tool. PANGÉIA, the game we developed, was based on the GURPS system and to be placed at the geological Eras of the earth. The objective of the game was playing a character that represented an animal belonging to a Class of Vertebrates, and making it surviving and reproducing during risky situations presented in the game. These situations were narratives by the Master about challenges that the character would face, which should be solved using the dices. Along the narrative, the Master introduced concepts and informations about the subject being studied. To evaluating how the game worked out, we solicited 11 volunteers, from two different schools in Natal, to play PANGÉIA. Before starting the game, and without knowing the final objectives of our project, the volunteers answered a general questionnaire to let us know their level of knowledge, which was also answered after playing the game. The comparison of the volunteers answers before and after playing the game suggests that this activity influenced them. Also, based on this test, we identified critical aspects to be modified in PANGÉIA, specially a stronger relation between both the questionnaire and the game placement with the narrative of the master. In order to have PANGÉIA used as a complementary learning tool, a teachers handbook has to be written, including rules concerning the format of game application. Nonetheless, based on this pilot study, we conclude that topics on sciences and biology can be easily adjusted to RPG format, and its flexibility provides multiple combinations that can be used to help learning the more difficult topics to be taught in a class